Stewardship of personal data on social networking sites. (February 2021) - Angelopoulos, Spyros; Brown, Michael; McAuley, Derek; Merali, Yasmin; Mortier, Richard; Price, Dominic
Highlights: We propose a conceptual design to overcome the challenges of storage, analysis, and integrity associated with stewardship of personal data. We take a systemic perspective, shifting from a user-provider relationship to a more symbiotic one in which users have control over their data. We apply our design to social networking sites to address problems of privacy and identity and pave the path to a richer set of possible applications. We discuss the significance of our work for the management of personal data and its importance for future research and the design of online platforms. Abstract: The extant Information Management literature highlights the asymmetric distribution of power between users and online platforms, while the issues related to the stewardship of personal data on such platforms remain problematic and largely unresolved. To address that lacuna, we propose a conceptual design that can help to overcome many of the challenges related to storage, analysis, and integrity associated with the stewardship of personal data on online platforms. We adopt a systemic perspective and propose a shift from the current user-platform relationship to one in which users control the level of access to their data, organisations are relieved from the burden of maintaining personal data, and the data are not decoupled from information about their provenance and context of origin. We apply our conceptual design to the context of social networking sites, where we specifically address issues related to privacy, and identity and pave the path to a broader set of possible applications. We discuss the significance and timeliness of our proposed conceptual design for the stewardship of personal data, and the importance of our findings for future research, as well as for the design of online platforms.